ACMS: a database of alternate conformations found in the atoms of main and side chains of protein structures. Issue 4 (25th June 2019) - Santhosh, R.; Chandrasekaran, P.; Michael, Daliah; Rangachari, K.; Bankoti, Namrata; Jeyakanthan, J.; Sekar, K.
Abstract : An online knowledge base on the alternate conformations adopted by main‐chain and side‐chain atoms in protein structures solved by X‐ray crystallography is described. Abstract : Proteins are usually dynamic biological macromolecules, thereby exhibiting a large number of conformational ensembles which influence the association with their neighbours and interacting partners. Most of the side‐chain atoms and a few main‐chain atoms of the high‐resolution crystal structures deposited in the Protein Data Bank adopt alternate conformations. This kind of conformational behaviour prompted the authors to explore the relationship, if any, between the alternate conformations and the function of the protein molecule. Thus, a knowledge base of the alternate conformations of the main‐ and side‐chain atoms of protein structures has been developed. It provides a detailed description of the alternate conformations of various residues for more than 60 000 high‐resolution crystal structures. The proposed knowledge base is very user friendly and has various flexible options. The knowledge base will be updated periodically and can be accessed athttp://iris.physics.iisc.ac.in/acms .